Estudio definitivo a nivel de ejecución de la carretera Chambira Cunchuhuillo - Rubina Perdomo, Tony (2005)
The present Thesis work to choose the Professional Title of Civil Éngineer, has been developed with the purpose of carrying out a contribution technical-scientist to contribute to salve a problem of local variety, that to the executed being will allow to tell on a wagon section that it will help to the socioeconomic development of the benefited population. The applied investigation is of type and it has been carried out in the Faculty of Civil Engíneering, of the National University of San Martín, developing the project in the Province of Mariscal Cáceres, Region of San Martín. This work has been developed applying on the land the theories and existing norms of topography, ground mechanics, environmental impact, hydrology, road, concrete drainage and other relatives by marriage, and that have allowed to count on the definitive study of the wagon section already named. The results demonstrate obviously that it is possible to obtain, from the correct application of the theories, alternative, forceful studies and results that soon of the moderate analysis can be presented/displayed in form of definitive project, evaluating their feasibility in their entire context, optimizing their road. This, actually means that the elaborated project had an evaluation of alternative routes having itself determined but the optima! one and settling down the most advisable budget, which gives a feasible project us to execute, putting it to disposition of which it corresponds, to transact its financing and execution, doing possible that the National University of San Martín executes it's contribution in favor of the Sanmartinense society.